2011
DOI: 10.1016/j.socscimed.2011.02.036
|View full text |Cite
|
Sign up to set email alerts
|

‘All is done by Allah’. Understandings of Down syndrome and prenatal testing in Pakistan

Abstract: Understanding the psychosocial impact of a congenital condition such as Down syndrome on affected individuals and their family requires an understanding of the cultural context in which they are situated. This study carried out in 2008 used Q-Methodology to characterize understandings of Down syndrome (DS) in Pakistan in a sample of health professionals, researchers and parents of children with the condition. Fifty statements originally developed for a UK study and translated into Urdu were Q-sorted by 60 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
(35 reference statements)
4
35
0
2
Order By: Relevance
“…There was also a strong sense amongst both the Christian and Muslim believers that people do not have the right to interfere and that one was chosen by God to have a child with DS. These findings are similar to those reported amongst Christian mothers of children with disabilities in the USA by Landsman (2005) or Michie and Skinner (2010), as well as amongst Muslim women in Pakistan by Bryant et al (2011) or Muslim women in Australia (Tsianakas and Liamputtang 2002).…”
Section: Discussionsupporting
confidence: 88%
“…There was also a strong sense amongst both the Christian and Muslim believers that people do not have the right to interfere and that one was chosen by God to have a child with DS. These findings are similar to those reported amongst Christian mothers of children with disabilities in the USA by Landsman (2005) or Michie and Skinner (2010), as well as amongst Muslim women in Pakistan by Bryant et al (2011) or Muslim women in Australia (Tsianakas and Liamputtang 2002).…”
Section: Discussionsupporting
confidence: 88%
“…When looking at the attitudes of parents of children with Down syndrome towards prenatal testing in general, it seems that most believe prospective parents should have autonomy and reproductive freedom (Inglis et al 2012; Scott et al 2013). However, studies have shown cultural and religious differences in attitudes towards prenatal testing and termination of pregnancy amongst parents of children with Down syndrome (Ahmed et al 2013; Bryant et al 2011). A study of 78 women who had a sibling with Down syndrome showed that they overall had a positive experience of having a brother or sister with this condition, but around one-third would still consider prenatal testing and termination of pregnancy since they experienced a negative impact on themselves and their family (Bryant et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We found that women interpreted informed choice in antenatal screening in different ways, challenging policy assumptions that all women want to make decision about antenatal screening without advice from healthcare professionals. Some women, particularly those from minority ethnic groups, wanted health professionals to give advice and make recommendations 19. The findings had implications for the role of health professionals in providing information and supporting informed decision making, to improve quality of care and equity of access.…”
Section: Understanding Challenges In Healthcare Policy With Q-methodomentioning
confidence: 99%
“…This study aimed to explore perceptions of informed choice in antenatal screening in women from China, Hong Kong and Pakistan. The Q-set was adapted from a similar study conducted within the UK 19. Participants were women with at least one child aged under 3 and the study was conducted in China, Hong Kong and Pakistan.…”
Section: Understanding Challenges In Healthcare Policy With Q-methodomentioning
confidence: 99%